Ragnarok: The end of time? Revelation or “Destiny of the Powers” in the Norse Mythological Universe - Sierra del Molino, Rosa María (ARYS. Antigüedad: Religiones y Sociedades, 2019)
This paper examines whether the revelation of Norse mythology or “Ragnarök” is really the end of time or the end of the world, and the extent that this cataclysm would not affect all beings of the universe alike, including the main divinities. For this reason, we will try to give an interpretation of the symbolic and key role that Ragnarok played in the Scandinavian mental universe.
Keywords: Ragnarök; Apocalypse; Fate; Time; Pact; oath; regeneration